History of Shabbir Akhtar's Thoughts on Islam as a Political Religion - Isra Hasanah; Miftah Nidaul Jannah Siregar; Elly Warnisyah Harahap (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Akhtar in his work entitled “The Quran and The Secular Mind” argues that Islam is unique in its decisions and capacity to face, rather than accommodate, the challenges of secular beliefs. Moreover, Islam does not have a preference for an established political system but only has a set of ethical values that can be used as guidelines for the administration of political life. This became the basis of Shabbir Akhtar's philosophy to refer to Islam as a political religion, through the history of the Prophet Muhammad which was criticized by Kenneth Cragg in his books entitled “Muhammad and the Christian” (1984) and “Readings in the Quran” (1988).